Effect of roughness in full-scale validation of a CFD model of self-propelled ships. (June 2020) - Mikkelsen, Henrik; Walther, Jens Honoré
Highlights: A ship scale self-propulsion CFD setup with free surface and rotating propeller has been developed and validated in systematic steps in order to ensure accuracy. The discrepancies for resistance, open-water and model scale self-propulsion CFD simulations are found to be within the model test uncertainty. For the ship scale self-propulsion simulation, the delivered power from CFD is underestimated with 8–12% compared to the speed trial measurements when the roughness is estimated using the standard empirical formula by Townsin. By including a roughness model directly into the self-propulsion simulation, by modifying the wall functions, the discrepancy is significantly reduced. The study indicates that using a roughness model directly into the CFD simulation, could be more accurate than the traditional method using empirical formulas designed for towing tanks. Abstract: This paper presents a comparison of full-scale computational fluid dynamics (CFD) simulations with speed trial measurements for a ro-ro vessel and a general cargo vessel. Significant work has been done on validating CFD simulation in model scale. However, in full-scale very few publicly available studies have been conducted due to limited access of validation data. The present study includes extensive validation and verification of both resistance, propeller open-water and self-propulsion simulations in both model and full-scale. The self-propulsion simulations include modelling of the free surface and rotation of the 3D propeller. Full-scale resistance and propeller open-water as well as model scale self-propulsion simulations show good agreement with towing tank measurements and predictions. However, the full-scale self-propulsion simulations using the traditional approach of including the roughness as a point force estimated by an empirical formula significantly underestimate the power from the speed trial measurements. By including the effect of hull and propeller roughness directly into the CFD model, by modifying the wall functions, the discrepancy between CFD and speed trial measurements decreases significantly. This indicates that inclusion of a roughness model directly into the CFD simulation could be a more accurate method than the traditional approach of using empirical formulas originally designed for towing tank extrapolation.